PERLINDUNGAN HUKUM BAGI PIHAK BERKEPENTINGAN ATAS PROSES AKUISISI PT. BANK JASA ARTA OLEH PT. BANK RAKYAT INDONESIA Tbk - Sabri Fataruba (Faculty of Law, Universitas Pattimura, 2011)
Corporate action is dead of law generating impact for all the stockholders, either at requisitionist company and also target company. In Bank context must be paid attention is, minority stockholder, bank creditur, related to protection of law for the side of intended. This thing needs, remember one of impotant element from acquisition is element fairness applied for all party. Related to the intended, hence in process of requisitionist, the bank its the must has paying attention to rules applied, that is invitors number 40 the year 2007 about Limited Liability, number Code 10 the year 1998 about change to number Code 7 year 1992 about Banking, number Code 8 the year 1995 about Capital Market, Indonesia Bank Rules and Keputusan BAPEPAM arranging about Acquisition Procedure for Public Corporation. Intention of at paying attention to order or rule aplied arranging about acquisition for public corporation is for the agenda of giving protection to interested parties, either at requisitionist company or at company target, so that the interested parties nothing that is harmed with existence of acquisition is intended.